The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3390/nano9050664
|View full text |Cite
|
Sign up to set email alerts
|

SERS-Active Substrate with Collective Amplification Design for Trace Analysis of Pesticides

Abstract: Health risks posed by the exposure to trace amounts of pesticide residue in agricultural products have gained a lot of concerns, due to their neurotoxic nature. The applications of surface-enhanced Raman Scattering (SERS) as a detection technique have consistently shown its potential as a rapid and sensitive means with minimal sample preparation. In this study, gold nanoparticles (Au NPs) in elliptical shapes were collected into a layer of ordered zirconia concave pores. The porous zirconia layer (pZrO2) was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…With varying concentrations of R6G, a trend was observed wherein the logarithmic values of R6G concentrations and the intensities of the peak at 1361 cm −1 appeared to be a linear calibration plot as shown in Figure 3d. This indicates that the substrate holds a potential in quantitative determination of analyte even with only SERS peak intensity is given, as also observed in some studies [15,16].…”
Section: Evaluation Of the Sers Effect Of Ag Nsps_x/tapesupporting
confidence: 76%
See 1 more Smart Citation
“…With varying concentrations of R6G, a trend was observed wherein the logarithmic values of R6G concentrations and the intensities of the peak at 1361 cm −1 appeared to be a linear calibration plot as shown in Figure 3d. This indicates that the substrate holds a potential in quantitative determination of analyte even with only SERS peak intensity is given, as also observed in some studies [15,16].…”
Section: Evaluation Of the Sers Effect Of Ag Nsps_x/tapesupporting
confidence: 76%
“…While it is highly preferred that NSPs agglomerate to some degree, heavy agglomeration may not always provide an optimized SERS-active effect coming from a particular NSP. As compared with the case of a study utilizing Au NPs, a decrease in the peak intensities was observed when Au NPs were observed to be heavily clustered [15]. shown in Figure 2e, showing randomly-oriented Ag NSPs featuring blunt-tipped spikes, and a single Ag NSP could be distinguished in Figure 2f.…”
Section: Surface Characterization and Agglomeration Behavior Of Ag Nsmentioning
confidence: 79%
“…Based on the equations (2.1), (2.2), and (2.3), I SERS is the Raman signal intensity at 1361 cm −1 for each substrate, I Bulk is 25 after Raman spectral analysis, N Bulk is estimated around 3.9 × 10 10 molecules, and N SERS is estimated as a value of 2.6 × 10 6 . The results indicate that (1) the EF of Ag HNS shows slightly higher as the size and dimension of cavity is smaller [16]; (2) all the Di NPs/Ag HNS_130 have EFs significantly higher than Ag HNSs and greater than 10 7 ; (3) Al 2 O 3 /Ag HNS_130 has the largest EF with a value of 6.2 × 10 7 , which also shows that Ag HNS with the attachment of lower dielectric constant NPs results in a high EF [44]. Note that the values of dielectric constant for Al 2 O 3 , HfO 2 , and TiO 2 / are 9-10, 20-30, and 10-85, respectively [46,47].…”
Section: Sers Property Of DI Nps/ag Hnsmentioning
confidence: 92%
“…A lipid-removal procedure, as described in Experimental section, was thus necessarily prior to the sample into the detection [50,51]. The peak found at 1035 cm −1 presumably resulted from the surface of Al2O3 NPs/Ag HNS, which is likely the background thar contributed by the core shell structure of Ag HNS [52,53] and Al2O3 NPs upon Ag HNS, in the case of ampicillin in milk solution [44]. In Figure 6b, by taking these three peaks and low concentration (i.e., 0.01 ppm) of ampicillin in water and milk solution for a comparison, the results show the influence of ampicillin in different solutions.…”
Section: Nps/ag Hns For Trace Detection Of Ampicillin In Milk Solumentioning
confidence: 99%
See 1 more Smart Citation